Walk Off Winning - Trimper, Steve (Ascent Audio, 2020)
There are many books available on the topic of leadership, but none quite like this one. Walk Off Winning: A Game Plan for Leading Your Team and Organization to Success is the work of Steve Trimper-a college baseball coach who shares what he has learned about business through his extensive leadership experience in high-level sports. In addition to reflecting on his own failures and successes, Trimper interviews leadership experts to distill a wealth of wisdom into this valuable book. With this book, you'll learn about the key principles of team building, culture, and organization building. If you are looking for a way to enhance your leadership, whether you lead a team of one or an entire organization, Walk Off Winning is for you. This book will give you the motivation and strategies to "become a doer." Anyone involved in leadership, sports management, or the general business world will benefit from the inspirational anecdotes and honest advice in this much sought-after guide for leaders of all kinds. From the sports field to the business office, good leadership in any arena shares a single, universal foundation. If you want to achieve your dreams, you'll have to learn to Walk Off Winning.